Description principles and their adherence to MARC 21 and ONIX formats - Serra, Liliana Giusti [UNESP]; Segundo, José Eduardo Santarem [UNESP]; Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP]; Zafalon, Zaira Regina [UNESP] (My University, 2017)
The article discusses the principles of description, analyzing the work The intellectual foundation of information organization, by Elaine Svenonius, published in 2000. It is a bibliographic research that analyzes the principles of description identified by the author in the aspects of user convenience, common use, representation, accuracy, sufficiency, need, standardization and integration; and seeks to identify the presence of these principles in the formats of representation. The formats of representation are analyzed as a result of their use in the description of the elements of bibliographic resources, so that they are machine-readable and interchanged between bibliographic systems. As formats of representation are used for the exchange of data and information, it was felt the need to verify if they are in line with the principles of description. The formats of representation used by libraries (MARC 21) and the publishing market (ONIX) were analyzed. Brief history and evolution of the two formats are presented, as well as the objectives that guided their development. The article concludes that the formats of representation analyzed have adherence to the principles of description that were analyzed. The article ends by pointing out the conformities of the MARC 21 and ONIX formats to the principles of description.
Los principios de descripción y su adherencia a los formatos MARC 21 y ONIX
Os princípios de descrição e sua aderência aos formatos MARC 21 e ONIX
Keywords: Cataloguing; Cataloguing principles; MARC 21 Format; ONIX Format